Färsk ved till Hallstaviks pappersbruk - Kogler, Fredrik (SLU/Dept. of Forest Products, 2004)
Hallstaviks papermill is an industry plant within Holmen Paper. Hallstavik is a mechanical mill and produce newspaper and journal paper. During year 2000, Hallstavik used approximate 1.200 m3f spruce, either as logs or chips from sawmills. Due to that the production is running continuously the mill also needs raw material at the same rate. At some periods the supply of raw material cannot keep up pace. Especially during the summer the cutting and the production at the sawmills decrease. In order to keep the production running at Hallsta during that period, they need to store raw material, mainly logs at the production site. That is costly, both regarding capital binding and quality deterioration, depending on how long time the logs are stored.